Can bone marrow aspirate concentrate change the mineralization pattern of the anterior maxilla treated with xenografts? A preliminary study - André Antonio Pelegrine; Marcelo Lucchesi Teixeira; Marcelo Sperandio; Thiago Sousa Almada; Karl Erik Kahnberg; Paulo José Pasquali; Antonio Carlos Aloise (Wolters Kluwer Medknow Publications, 2016)
Objective: To evaluate bony reconstruction of the atrophic anterior maxilla using particulate grafts with or without autologous bone marrow aspirate concentrate (BMAC). Materials and Methods: Eight patients with atrophy of the anterior maxilla due to teeth loss were selected and split into groups according to the type of material used: Control Group (CG) (n = 4) - particulate xenograft only and Test Group (TG) (n = 4) - a combination of particulate xenograft and BMAC. Both groups received a collagen membrane to cover the xenograft. After 4 months, during implant placement, a sample of bone was removed from the graft area using a 2 mm diameter trephine bur. The specimens were fixed and preserved for histomorphometric evaluation, which included the following parameters: Mineralized tissue (MT) and non-MT (NMT). Cone beam computed tomography was performed at 3 time intervals to measure bone thickness: (1) Before grafting, (2) 4 months and (3) 8 months postgrafting, using localized bone gain (mm) as the outcome variable. Results: Tomographic analysis revealed bone gain in CG of 3.78 ± 1.35 mm and 4.34 ± 1.58 mm at 4 and 8 months, respectively. TG showed an increase of 3.79 ± 0.52 mm and 4.09 ± 1.33 mm after 4 and 8 months, respectively. Histomorphometric analysis revealed that, for CG, MT- and NMT-related values were 52.3% ± 16.78% and 47.70% ± 5.55%, respectively, whereas for TG, they were 65.04% ± 20.98% and 34.96 ± 10.38, respectively. Conclusion: Although radiographic bone gain appeared similar between the groups, the use of BMAC obtained via the BMAC® method revealed an increased mineralization trend in the anterior maxilla. It must be highlighted, however, that this is a preliminary study with a relatively small sample population and further studies with larger sample sizes are needed to verify these results.